A Comparison of the Effectiveness of Parenting Education based on Acceptance and Commitment, and Parenting based on Positive Psychology in Improving Resilience and Mother-Child Relationship in Mothers of Children with Attention Deficit Hyperactivity Disor - Banani, Mahboobeh; Amini, Naser; Borjali, Mahmoud; Keykhosrovani, Moloud (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to compare the effectiveness of parenting education based on acceptance and commitment and parenting based on positive psychology in improving resilience and mother-child relationship in mothers of children with attention deficit hyperactivity disorder (ADHD). Method: The present study had a quasi-experimental method with a pretest-posttest design with a control group and a two-month follow-up. The statistical population consisted of mothers of 8 to 12-year-old boys with attention deficit hyperactivity disorder in Tehran. After screening with Connor-Davidson Resilience Scale (CD-RIS) (2003) and Pianta's Child-Parent Relationship Scale (CPRS) by purposive and convenience sampling, 45 mothers were selected and randomly assigned to two experimental groups a control group. The experimental group of parenting based on acceptance and commitment was intervened based on Quinn and Morrell protocol (2009), and the experimental group of positive psychology based on Seligman protocol (2005) was intervened for eight 90-minute sessions. Data were analyzed using repeated-measures analysis of variance. Results: Parenting education based on acceptance and commitment in improving resilience (F=5.38, P=0.029), and mother-child relationship (F=7.95, P=0.009), and parenting education based on positive psychology were effective in improving resilience (F=5.59, P=0.027), and mother-child relationship (F=6.07, P=0.021) in mothers of children with attention deficit hyperactivity disorder, and the effect was stable in the follow-up phase (p